EXPLORING CHALLENGES AND OPPORTUNITIES IN THE IMPORT OF FRUITS AND VEGETABLES IN INTERNATIONAL MARKETS - Kaur, Nainpreet; Singh, Veer Virendra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The global commerce of fruits and vegetables has experienced substantial changes in recent decades, influenced by evolving consumer preferences, developments in agricultural technology, and alterations in international trade rules. This study seeks to examine the problems and opportunities related to the importation of fruits and vegetables in global markets, with specific emphasis on the impact of World Trade Organisation (WTO) laws on their competitiveness in home markets. This paper assesses the influence of WTO agreements on market access, tariff barriers, and domestic agriculture laws using an extensive literature review and analysis of secondary data from credible sources. The findings indicate that although WTO policies create possibilities by lowering trade barriers and promoting competition, importers encounter difficulties including adherence to rigorous quality requirements and local regulations that favour domestic producers. The study elucidates the interaction of WTO policies, consumer preferences, and domestic market dynamics, offering significant insights for importers, retailers, and policymakers. The study indicates that comprehending these dynamics is essential for improving the competitiveness of imported fruits and vegetables in a progressively integrated global market.